INFLUENCE OF WORK LIFE BALANCE AMONG WOMEN’S EMPLOYEES IN ACADEMIC SECTOR - N. SUBHA DHARSINI,; T. S. AARATHY, (The Bioscan, 2026)
This research article seeks to “examine how work-life balance factors influence employee dedication within the education sector.” The study utilizes data reduction through Exploratory Factor Analysis (EFA) on a participant group of 480 individuals selected from educational establishments in Bengaluru and distills a collection of 16 work-life balance statements into five key factors. The current research presents a model outlining how work-life balance factors affect employee dedication in the education sector. The findings suggest that elements such as the work environment, the ability to make decisions, individual roles, and support at work, and interpersonal conflicts among colleagues significantly influence employee dedication within the education sector. Consequently, human resource managers in educational institutions should prioritize these elements to enhance employee commitment. This research assessed the Influence of work life balance among women’s employees in academic sector. Multiple linear regression analysis indicates that the work environment, decision-making authority, personal roles, work-related support, and conflicts with colleagues considerably affect employee dedication in the education sector. Keywords Work Life Balance, Working Environment, Personal role, women’s employees in academic sector.